2006
DOI: 10.1161/01.str.0000196984.90718.8a
|View full text |Cite
|
Sign up to set email alerts
|

Infratentorial Abnormalities in Vascular Dementia

Abstract: Background and Purpose-Infratentorial abnormalities may cause cognitive deficits, but current research criteria for vascular dementia (VaD) do not consider them. Our purposes were to determine the prevalence of infratentorial abnormalities in VaD, their relation with supratentorial abnormalities, and whether they are relevant to cognition. Methods-We examined 182 patients (120 men, mean ageϭ73 years, SDϭ8) with probable VaD at inclusion into a multicenter clinical trial. MRI scans were evaluated for infratento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…In patients with VP, brainstem and cerebellar involvement have been previously reported on MRI [3], and degenerative changes in the ipsilateral substantia nigra could occur 2 weeks after a striatal stroke [26]. Second, the midbrain atrophy could be related to global cortical atrophy, most probably attributable to axonal degeneration secondary to supratentorial pathology [10]. The association of midbrain atrophy and cognitive performance, in VaD patients, supports this hypothesis [10].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In patients with VP, brainstem and cerebellar involvement have been previously reported on MRI [3], and degenerative changes in the ipsilateral substantia nigra could occur 2 weeks after a striatal stroke [26]. Second, the midbrain atrophy could be related to global cortical atrophy, most probably attributable to axonal degeneration secondary to supratentorial pathology [10]. The association of midbrain atrophy and cognitive performance, in VaD patients, supports this hypothesis [10].…”
Section: Discussionmentioning
confidence: 80%
“…Second, the midbrain atrophy could be related to global cortical atrophy, most probably attributable to axonal degeneration secondary to supratentorial pathology [10]. The association of midbrain atrophy and cognitive performance, in VaD patients, supports this hypothesis [10]. We are not able to conclude whether midbrain atrophy is related to parkinsonism or to axonal degeneration.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a recent report on infratentorial abnormalities in vascular dementia, 11% of patients were found to have midbrain atrophy, as determined by an AP diameter of the mesencephalon less than 15 mm. Moreover, vascular dementia patients with midbrain atrophy are reported to have worse general cognitive and executive functions than those without midbrain atrophy; the midbrain was found to contribute to cognition independently of supratentorial structures [2]. Senile plaques, with or without neurofibrillary tangles in the periaqueductal gray and dorsal raphe nucleus of the midbrain was reported in Alzheimer's disease [15].…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have suggested that a low midbrain diameter on routine MRIs may be valuable in discriminating PSP from either Parkinson's disease or multiple system atrophy [6,14,17,24,27,28,35]. Recently, midbrain atrophy on MRIs, along with infratentorial vascular lesions, cerebellar atrophy, and changes in basilar artery diameter, have been reported for vascular dementia [2]. In particular, 11% of vascular dementia patients were found to have midbrain atrophy, which was determined by an anteroposterior diameter of the mesencephalon of less than 15 mm.…”
Section: Introductionmentioning
confidence: 99%